Merenggut Masa Depan: Menakar Dampak Pernikahan Dini pada Remaja dalam Cengkeraman Tradisi dan Kesenjangan - Diajeng Arum Sari; Candra Prawira; Desita Wulandani; Safna Kumalasari; Ilva Syukria; Didi Pramono (Lembaga Pengembangan Kinerja Dosen, 2024)
Early marriage is a phenomenon that is rampant in society, especially teenagers. Tradition and gender inequality are the main factors of early marriage. Significant impacts are experienced by adolescents due to early marriage. This study aims to describe the impact of early marriage on adolescents caused by traditional factors and gender gaps. The research method used is literature study analysis and documentation study by observing documentary videos. Coding and tabulation processes were carried out to test the validity and reliability of the data. The results showed that early marriage in adolescents is influenced by tradition and the gender gap. This suggests factors such as family pressure, local traditions, and lack of opportunities in education may reinforce the practice of early marriage. Emile Durkheim's structural functional theory analysis also highlights how early marriage functions in maintaining social stability, but also emphasizes the need to reduce the negative impact on gender inequality. Concrete measures such as sexual education, women's empowerment, and policy changes are needed to address the problem of early marriage in adolescents.